SIMULATION OF CO2 INJECTION IN A DEPLETED GAS RESERVOIR: A CASE STUDY FOR UPPER MIOCENE SANDSTONE, NORTHERN CROATIA - Amalia Lekić; Lucija Jukić; Maja Arnaut; Marija Macenić (Rudarsko-geološko-naftni Zbornik, 2019)
Carbon capture and storage (CCS) technology is a beneficial greenhouse gas mitigating strategy carried out in the last 20 years. Depleted gas reservoirs are promising candidates for the storage of carbon dioxide (CO2). Therefore, a depleted gas reservoir in the Upper Miocene sandstone located in Northern Croatia was taken as an example. The purpose of this study was to compare CO2 storage capacity obtained with two analytical equations to total storage capacity obtained through the simulator, in order to validate the equations. The first equation takes the average reservoir pressure and available production data into account, while the other one is more general and includes produced volume, CO2 density and formation volume factor of the original fluid. The tools used for these calculations were Schlumberger PVTi software, in which the equation of state was obtained, and ECLIPSE (E300 Module) which is a reservoir engineering simulator used for reservoir behaviour prediction. The results conformed analytical solutions, indicating that, depending on the depth, the mass of the CO2 that can be injected is twice as big as the mass of CH4 produced. The results of analytical solutions, 16.7 × 106 m3 and 14.6 × 106 m3, are in accordance with the results obtained by the simulation of CO2 injection in depleted reservoirs - 16.2 × 106 m3. Based on this, a conclusion is derived that these analytical solutions can be used as a first approximation of injection in a depleted gas reservoir.